Cause-Related Marketing and Strategic Agility: An Integrated Framework for Thriving in a Dynamic Environment - Christofi, Michael; Leonidou, Erasmia (My University, 2012)
This article posits a framework that illustrates how the concepts of strategic agility and causerelated marketing are synthesized in order to generate a sustainable competitive advantage through superior brand awareness and positive corporate reputation. This paper reflects how CRM and strategic agility in the context of creating and sustaining a competitive advantage in a hyper-dynamic environment, can complement and magnify each other's traditional context of analysis. Moreover, this article appears to be the first of its kind to theoretically examine the dynamics implied by synthesizing these, so far, distinct concepts. In conclusion, the paper posits a set of research directions designed to enable scholars to further advance the integration of strategic agility and CRM from both problem-driven theory development as well as theorydriven practice management perspectives
Keywords: Brand awareness; Corporate reputation; Strategic agility; Cause-related marketing; Competitive advantage